KEPATUHAN TERHADAP STANDAR KESELAMATAN KERJA DI INDUSTRI KULINER STUDI ANALISIS: KASUS RUMAH MAKAN SATE XYZ & SHIN YUEN BANDUNG - Akib, Muhammad Syakib Asqalani Rifai; Pandu Sapto Desmantyo (JURNAL MANAJEMEN KULINER, 2024)
This study centers on the enforcement of occupational safety regulations in the culinary industry, with a focus on Rumah Makan Sate XYZ & Shin Yuen restaurant in Bandung. Due to the high potential for accidents and health-related issues in kitchen and restaurant settings, the primary objective was to assess adherence to existing occupational safety standards, their effectiveness, and to identify potential risks. Initial findings reveal a lack of emphasis on occupational safety in the culinary sector, including at Rumah Makan Sate XYZ & Shin Yuen, where safety training and the use of personal protective equipment are notably limited. This underscores the suboptimal implementation of work safety standards at Sate XYZ & Shin Yuen, evident from inadequate safety training, insufficient use of personal protective equipment, and a lack of awareness about work safety protocols. Nonetheless, the study also uncovered a positive correlation between compliance with safety standards, increased productivity, and employee well-being. For this study, 8 workers at the XYZ Satay Restaurant & Shin Yuen Restaurant served as participants and interview subjects. The research enlisted informants from three distinct groups: representatives from academia, restaurant management, and relevant associations. The recommended strategies to enhance work safety practices encompass regular training, ensuring the availability of adequate personal protective equipment, and initiatives to raise employee awareness about work safety. Furthermore, the involvement of partners in providing resources and support to establish improved safety standards in the culinary sector was deemed significant. Implementation of these recommendations is anticipated to foster a safer and more conducive work environment.